Biomechanical modeling of the physical training of girls during aerobic activities in non-school educational institutions - I.P. Supilo (Physical Education of Students)
Purpose : to validate the effectiveness of biomechanical modeling of physical training of girls. Material : the study involved 90 girls aged 16-18 years (60 girls and recreation groups and 30 - sporting group aerobics). Results : during the study of quantitative biomechanical characteristics of the physical training of girls was identified the quantitative biodynamic and coordination structure of motor characteristics during aerobics. When comparing girls identified the best girls sports group thus constructed biomechanical model. For the considered model biodynamic structure includes the following indicators: GRAD; Fz max; Tmax; F max; Tsum; G; Tps. To the graphic model of the coordination patterns included the following indicators: EllS; MO(x); LY mm; Lх mm; JEF %;V mm/s; IV; R mm. Conclusions : obtain the quantitative biomechanical model of indicators of physical training of girls, which is the basis for objective justification and development of a technique of aerobics, and to use these biomechanical models as a control and the future of forecasting.